Digitalisasi Layanan Kesehatan: Tantangan Etika dan Keamanan Data Pasien - Pirma Ivan Ricky Manurung; Marice Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The digitalization of healthcare services has emerged as a pivotal catalyst in modernizing Indonesia’s health system, delivering enhanced efficiency, accessibility, and integrated service quality. This study employs a qualitative literature review approach to explore the implementation of digital transformation strategies in hospitals, with a particular emphasis on ethical challenges and patient data security. The findings reveal that the adoption of technologies such as artificial intelligence, Internet of Things, and telemedicine accelerates service delivery and broadens medical outreach, especially in remote areas. Nevertheless, critical issues arise concerning the vulnerability of health data to breaches, misuse, and cyber threats, exacerbated by uneven digital infrastructure and limited technological literacy among healthcare professionals. Proposed strategies include strengthening data protection regulations, improving human resource capacity, and fostering cross-sectoral collaboration to establish a secure and ethical digital healthcare ecosystem. Through comprehensive management of these challenges, healthcare digitalization is expected to expedite the achievement of SDG 3 and bolster public trust in the national health system.